Factors Leading to Delay in Diagnosis of Myasthenia Gravis - Farooq, Maheen; Abrar, Ateeba; Nisha, .; Muhammad, Fatima Ghulam; Devi, Lata (Biological and Clinical Sciences Research Journal, 2025)
Myasthenia gravis (MG) is a chronic autoimmune neuromuscular disorder with variable presentations, often mimicking other conditions, which leads to delayed diagnosis. Early identification and management are critical to prevent morbidity and improve prognosis. In resource-limited settings like Pakistan, diagnostic delays may be influenced by clinical, systemic, or diagnostic limitations. Objective: To determine the factors contributing to delayed diagnosis of myasthenia gravis among patients presenting to the Department of Neurology at Jinnah Postgraduate Medical Centre, Karachi. Methods: This cross-sectional study was conducted in Ward 28, Department of Neurology, Jinnah Postgraduate Medical Centre (JPMC), Karachi, from December 12, 2024, to April 13, 2025. After obtaining ethical approval from the institutional review board, a total of 172 patients aged 18–72 years of both genders, diagnosed with myasthenia gravis, were recruited through non-probability consecutive sampling. Data on demographic characteristics, presenting symptoms, duration before diagnosis, and treatment modalities were collected using a structured proforma. The primary outcome was the duration of diagnostic delay (≤1 year vs. >1 year). Chi-square tests were used for categorical variables, and a p-value <0.05 was considered statistically significant. Results: Among 172 patients, 87 (51%) experienced a diagnostic delay of more than one year, while 85 (49%) were diagnosed within one year of symptom onset. The most frequent presenting symptom was ptosis (32%), followed by diplopia (24%), dysphagia (23%), and generalized fatigue or muscle weakness (15%). Anticholinesterase therapy was the most common treatment modality (29%), followed by immunosuppressants (25%), plasmapheresis (24%), and IVIG (22%). Notably, 58% of patients with delayed diagnosis had negative laboratory test results compared to 42% in those diagnosed earlier (p = 0.022), indicating a statistically significant association. Conclusion: A substantial proportion of myasthenia gravis patients experience diagnostic delays exceeding one year. Non-specific initial symptoms and negative laboratory findings are major contributors. Enhancing clinical suspicion and improving diagnostic protocols in tertiary care settings may facilitate timely diagnosis and reduce disease burden.